Bezdzietność w Polsce - Vielrose, Egon (Wydział Prawa i Administracji UAM, 1981)
Childlessness is analyzed among married women aged 35 - 39 in 1970. A strong relationship was found between the proportion of childless women and the gross reproduction rate with a time-lag of 10 years. The respective regression equation seems, however not to be stable in time. The proportion of married women aged 30 - 34 having no children below age 16 might also serve to estimate the proportion of childless women.
Childlessness in Poland